2018
DOI: 10.5562/cca3294
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antioxidant Activity of Essential Oil Obtained from Bitter Orange Peel (Citrus aurantium L.) Using Two Methods

Abstract: In this study, it was shown that the chemical composition of the essential oil obtained from bitter orange peel (Aurantii amari flavedo, Citrus aurantium L., from Croatia) depends on the method of isolation. The peel essential oil was obtained by hydrodistillation and cold press method, and their chemical compositions were analyzed by gas chromatography-mass spectrometry (GC-MS). Twenty two components were characterized by mass spectra and linear retention indices. Limonene was found as dominant compound in bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 14 publications
4
12
0
Order By: Relevance
“…The DPPH and ABTS methods are based on the stabilization of radicals, and the absence of activity is justified by the difficulty of the terpene compounds present in the essential oil to donate a hydrogen to neutralize the radical. In agreement with the data obtained in this work, Radan et al did not find antioxidant activity using these methods when they evaluated essential oils from peels from two varieties of bitter oranges ( Aurantii amari flavedo and Citrus aurantium L.). These oils also contained a predominance of limonene (91.1% and 51.3%, respectively).…”
Section: Resultssupporting
confidence: 89%
“…The DPPH and ABTS methods are based on the stabilization of radicals, and the absence of activity is justified by the difficulty of the terpene compounds present in the essential oil to donate a hydrogen to neutralize the radical. In agreement with the data obtained in this work, Radan et al did not find antioxidant activity using these methods when they evaluated essential oils from peels from two varieties of bitter oranges ( Aurantii amari flavedo and Citrus aurantium L.). These oils also contained a predominance of limonene (91.1% and 51.3%, respectively).…”
Section: Resultssupporting
confidence: 89%
“…Previous studies were focused on antimicrobial and health-promoting activities of different parts of C. aurantium , such as fruits and flowers, as well as essential oils obtained thereof [ 13 , 14 , 15 ]. Furthermore, substantial research has been focused on the chemical composition of essential oils prepared from various parts of Citrus aurantium growing in Pakistan [ 16 ], Brazil [ 17 , 18 ], Morocco [ 19 ], Iran [ 20 , 21 ], Croatia [ 22 ], northern Tunisia [ 23 ], India [ 24 ], and Algeria [ 25 , 26 ]. Essential oils of C. aurantium were reported to be a source of bioactive compounds with antimicrobial [ 19 , 21 , 23 , 27 ], antioxidant [ 19 , 22 , 23 ], anti-inflammatory [ 18 ], and anti-anxiety properties [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many studies have been focused to study chemical composition of the essential oils from various parts of Citrus aurantium growing in Pakistain (Kamal et al 2011), Brazil (Wolffendbuttel et al 2015Amorim et al 2016), Morocco (Ouedrhiria et al 2015), Iran (Khakpourk et al 2014;Azhdarzadeh et al 2016), Croatia (Radan et al 2018), northern Tunisia (Trabelsi et al 2014), India (Periyanayagam et al 2014) and Algeria (Abderrazak et al 2014;Djenane 2015). In addition, it has been reported that essential oils of C. aurantium were a source of bioactive compounds, they have been recognized as antimicrobial (Trabelsi et al 2014;Ouedrhiria et al 2015;Azhdarzadeh et al 2016), antioxidant (Trabelsi et al 2014;Ouedrhiria et al 2015;Radan et al 2018), antiinflammatory (Amorim et al 2016) and anti-anxiety agent (Khakpour et al 2014).…”
mentioning
confidence: 99%